Effects of running fatigue on lower extremity symmetry among amateur runners: From a biomechanical perspective - Gao, Zixiang; Fekete, Gusztáv; Baker, Julien S.; Liang, Minjun; Xuan, Rongrong; Gu, Yaodong (Frontiers in Physiology, 2022)
The objective of this study was to examine the effects of running fatigue on the symmetry of lower limb biomechanical parameters in eighteen male amateur runners. The marker trajectories and ground reaction forces were collected before and after the running-induced fatigue protocol. Symmetry angles (SA) were used to quantify the symmetry of each parameter. Normality tests and Paired sample T-tests were carried out to detect bilateral lower limb differences and SA of parameters between pre- and post-fatigue. One-dimensional statistical parameter mapping (SPM_1d) was used to compare parameters with the characteristic of one-dimensional time series data of lower limbs. After fatigue, the SA of knee extension angles, knee abduction moment, and hip joint flexion moment increased by 17%, 10%, and 11% respectively. In comparison, the flexion angle of the knee joint decreased by 5%. The symmetry of internal rotation of ankle, knee and hip joints increased after fatigued, while the SA of external rotation of the three joints decreased significantly. These findings provide preliminary evidence that fatigue changes lower limb symmetry in running gait and may have implications for understanding running-related injuries and performance.